Carcinoma Cuniculatum with Bone Invasion Mimicking a Viral Wart - Isabela Guerra; Hisabella Lorena Porto Simões; Marcella Amaral Horta Barbosa Vieira; Maria Christina Marques Nogueira Castañon (Sociedade Portuguesa de Dermatologia e Venereologia, 2021)
Carcinoma cuniculatum is a rare variant of low-grade and well-differentiated squamous cell carcinoma. It is a locally invasive tumor, although it has low metastatic potential. It was originally described in the plantar region but may exceptionally appear in other locations. It predominates in middle-aged men and presents clinically as an exophytic, solitary, painful tumor, with insidious growth. Histologically, this tumor simulates a variety of benign dermatoses and may require several biopsies for the correct diagnosis. It is often misdiagnosed as a viral wart, due to the clinical similarity and the indolent course. The treatment of choice is surgical excision due to the high risk of recurrence and locally aggressive behavior. Amputation can be performed in cases of deep tissue invasion. We present a case of carcinoma cuniculatum in which the late diagnosis favored the invasion of the underlying bone, resulting in amputation of the affected finger.